Evaluation methods for retroreflectors and quantitative analysis of near-infrared upward reflective solar control window film—Part II: Optical properties evaluation and verification results. (15th May 2017) - Harima, Tatsuya; Nagahama, Tsutomu
Abstract: In recent years, cool materials that have high solar reflectivity and thermal emittance properties have been applied for building surfaces in the urban environment. However, when such highly reflective materials reflect all or part of the solar radiation downwards or towards the ground, there are concerns that it leads to deterioration of the thermal environment of pedestrian spaces. A newly developed near-infrared (NIR) upward reflective solar control window film (URSCF) has come to the market. The film reflects NIR upwards to the sky, and shields a building's interior from solar radiation without deteriorating the thermal environment of pedestrian spaces. In order to quantify the reflected solar radiation, it is necessary to clarify the reflectivity and transmissivity properties of retro-reflective materials, which is desirably performed through measurement in a stable environment using artificial light sources. This required development of the evaluation methods using apparatus including an integrating sphere, allowing the measurement of directional-hemispherical spectral reflectivity at large incident polar angles, as well as the selective measurement of directional-upward spectral reflectivity from retro-reflective surfaces. It was confirmed that these results are appropriate through verification with the results obtained from commercially available apparatus and from optical simulations. With respect to the effect of NIR URSCF, it was confirmed that downward reflectance of solar radiation at the incident polar angle of 70° and the incident azimuth angle of 0° was approximately half of that of conventional specular reflective solar control window film.